Microsporidiosis in Fish - Bunnajirakul, Sumrarn (Journal of Mahanakorn Veterinary Medicine, 2024)
Microsporidia infected in various species of fish such as zebra fish, ornamental fish in the neon group, Japanese eel direct contact was found as transmission route. Chronic infected fish presented cachexia concurrent with spinal deformities such as lordosis or scoliosis. Accumulation of spore was found in infected tissue. The standard verification method used transmission electron microscopy to identify the polar ﬁlament and internal structure of the spores. Good water treatment system, ultraviolet light sterilization including vector elimination should be considered for reduction the risk of infection in the farm.